2016
DOI: 10.4137/jen.s33444
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects against POCD by Photobiomodulation: Evidence from Assembly/Disassembly of the Cytoskeleton

Abstract: Postoperative cognitive dysfunction (POCD) is a decline in memory following anaesthesia and surgery in elderly patients. While often reversible, it consumes medical resources, compromises patient well-being, and possibly accelerates progression into Alzheimer’s disease. Anesthetics have been implicated in POCD, as has neuroinflammation, as indicated by cytokine inflammatory markers. Photobiomodulation (PBM) is an effective treatment for a number of conditions, including inflammation. PBM also has a direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 300 publications
(500 reference statements)
1
33
0
2
Order By: Relevance
“…It involves the deposition of the extracellular aggregates of β-amyloid, known as senile plaques, and the formation of neurofibrillary tangles that are intracellular inclusions mainly composed of hyperphosporylated tau [4]. POCD is a decline in memory following anesthesia and surgery and The risk factors of developing POCD mainly include larger and more invasive operations, duration of anesthesia, advanced age and other factors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It involves the deposition of the extracellular aggregates of β-amyloid, known as senile plaques, and the formation of neurofibrillary tangles that are intracellular inclusions mainly composed of hyperphosporylated tau [4]. POCD is a decline in memory following anesthesia and surgery and The risk factors of developing POCD mainly include larger and more invasive operations, duration of anesthesia, advanced age and other factors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches support the ability of light to penetrate the brain tissue and exert biological effects on photoacceptor molecules present in central nervous system structures . Several studies have shown its potential benefits in retinal diseases, stroke, neurodegeneration, neuromuscular disorders, and memory and mood disorders . In addition, the increase of the pain threshold in the right hindpaw of mice (measured by von Frey filaments) was demonstrated after photobiomodulation with infrared (810 nm) applied to different anatomical locations.…”
Section: Discussionmentioning
confidence: 94%
“…Potent neuroprotective effects have been demonstrated in various models of retinal damage, by red -633/NIR light, with limited data from human studies showing its ability to improve visual function. Improved neuronal mitochondrial function, increased blood flow to neural tissue, upregulation of cell survival mediators and restoration of normal microglial function have all been proposed as potential underlying mechanisms of red/NIR light[ [16,17].…”
Section: Discussion:-mentioning
confidence: 99%
“…Local helium-neon laser therapy contributes to the prevention of the inflammatory reaction and promotes local tissue proliferation and wound healing [13] LLLT is a special type of laser therapy in which the irradiation used is red or near infrared beams with a wavelength of 600 -1100 nm and an output power of 1 -500 mW. This type of radiation is a continuous wave or pulsed light which consists of a constant beam of relatively low energy density (0.04-50 J/cm 2 ) [14,15,16,17]. LLLT represents a novel therapeutic method that, other than surgical laser applications, does not damage tissues [18.19].…”
mentioning
confidence: 99%